2017
DOI: 10.1111/tri.12975
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibitors and risk of chronic antibody-mediated rejection after kidney transplantation: where are we now?

Abstract: Summary Antibody‐mediated rejection (AMR) usually starts with generation of donor‐specific anti‐HLA antibodies (DSAs), arising from a B‐cell response to antigen recognition. In vitro and preclinical data demonstrate that mammalian target of rapamycin (mTOR) inhibition attenuates the mTOR‐mediated intracellular signaling pathway involved in AMR‐related kidney damage. The limited available data from immunological studies in kidney transplant patients, however, have not shown such effects in vivo. In terms of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 84 publications
0
24
0
1
Order By: Relevance
“…In contrast with CNIs, direct effects on B cells of mTORi have been reported [53]. In vitro cultures of human B cells with mTORi showed a profound attenuation of B-cell activation and IgG production [30,31]. Moreover, sirolimus but not tacrolimus was able to inhibit the proliferation of B cells and their differentiation into plasma cells [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with CNIs, direct effects on B cells of mTORi have been reported [53]. In vitro cultures of human B cells with mTORi showed a profound attenuation of B-cell activation and IgG production [30,31]. Moreover, sirolimus but not tacrolimus was able to inhibit the proliferation of B cells and their differentiation into plasma cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is controversial data regarding the effect of mTORi conversion in other peripheral blood T cell subsets [20,[27][28][29]. Moreover, scarce and controversial data are available regarding peripheral blood B cells and NK cells and the use of mTORi [27,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…4 The chronic antibody-mediated rejection after sustained exposure to mTORi might influence the graft survival. 45 Recent meta-analysis and literature reviews provided the evidence that early withdrawal of CNI and introduction of mTORi might induce the de novo glomerulonephritis and graft loss. 46,47 However, the Cochrane database reported that mTORi might increase the acute rejection, but the effect on long-term graft loss was still uncertain.…”
Section: T a B L E 2 Demographic And Clinical Characteristics Of Mtmentioning
confidence: 99%
“…This is not surprising, as our traditional chronic immunosuppression regimens, usually consisting of an antiproliferative agent plus a CNI, primarily target T cells and not the humoral immune system. However, it has been shown that optimization of B‐cell antiproliferative IS based on CNIs is less likely to be associated with DSA development than IS based on inhibitors of the mTOR, especially if there is minimal variability in CNI trough levels . A recent pediatric study has shown that a reduction in MMF dosing below the recommended amounts, for example, for gastrointestinal or hematologic side effects, is associated with a significant increase in the risk for rejection, both cellular and humoral and also suggests that lower mycophenolic acid levels are associated with the formation of DSA …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that optimization of B-cell antiproliferative IS based on CNIs is less likely to be associated with DSA development than IS based on inhibitors of the mTOR, especially if there is minimal variability in CNI trough levels. 9 A recent pediatric study has shown that a reduction in MMF dosing below the recommended amounts, for example, for gastrointestinal or hematologic side effects, is associated with a significant increase in the risk for rejection, both cellular and humoral and also suggests that lower mycophenolic acid levels are associated with the formation of DSA. 10 DSA surveillance, as recommended by published consensus guidelines, 1 was implemented in our institution's pediatric kidney transplant program in mid-2015 after a leadership change.…”
mentioning
confidence: 99%